Charmonium Properties Using the Discrete Variable Representation (DVR) Method - A., Bhaghyesh (Advances in High Energy Physics, 2021)
The Schrödinger equation is solved numerically for charmonium using the discrete variable representation (DVR) method. The Hamiltonian matrix is constructed and diagonalized to obtain the eigenvalues and eigenfunctions. Using these eigenvalues and eigenfunctions, spectra and various decay widths are calculated. The obtained results are in good agreement with other numerical methods and with experiments.